2001
DOI: 10.1046/j.1442-2042.2001.00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Orthotopic neobladder reconstruction in elderly bladder cancer patients

Abstract: Background: We compared the clinical results of orthotopic neobladder reconstruction in elderly patients and those in younger patients retrospectively in order to verify whether age is a critical factor in selecting a method of urinary diversion. Methods: Following radical cystectomy for bladder cancer, 12 patients aged 75 or older and 17 patients under 75 who underwent orthotopic neobladder reconstruction between January 1992 and May 1999 were investigated in this study. The authors TS and BS were among the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 18 publications
(25 reference statements)
1
11
0
3
Order By: Relevance
“…[9], [13], [23], [28], [29] The healthcare system is different between China and US, patients in our institution often comes from different provinces, it’s not convenient for patients to find an rehabilitation center for medical support after discharging from hospital, so most patients preferred to stay until all the tubes and sutures were removed even if they were fit for discharge in the LRC group. Hemal et al [30] and Saika et al [31] considered hospital stay was sometimes a reflection of health-care mode and the prevalent social condition of the patients. Overall survival rate is the golden standard to evaluate the feasibility of a medical intervention, it was observed that the LRC not only achieved less complication but also gained comparable overall survival (81% vs. 76%, P = 0.746) compared with ORC at a median follow-up of 21 months (range 3–61 months).…”
Section: Discussionmentioning
confidence: 99%
“…[9], [13], [23], [28], [29] The healthcare system is different between China and US, patients in our institution often comes from different provinces, it’s not convenient for patients to find an rehabilitation center for medical support after discharging from hospital, so most patients preferred to stay until all the tubes and sutures were removed even if they were fit for discharge in the LRC group. Hemal et al [30] and Saika et al [31] considered hospital stay was sometimes a reflection of health-care mode and the prevalent social condition of the patients. Overall survival rate is the golden standard to evaluate the feasibility of a medical intervention, it was observed that the LRC not only achieved less complication but also gained comparable overall survival (81% vs. 76%, P = 0.746) compared with ORC at a median follow-up of 21 months (range 3–61 months).…”
Section: Discussionmentioning
confidence: 99%
“…Perioperatif mortalite 30 günlük ve 90 günlük olmak üzere iki şekilde tarif edilmiştir. [7,[18][19][20][21] Çalışmamızda perioperatif mortalite ilk 30 gün olarak değerlendirilmiştir. Hasta grubumuzda perioperatif mortalite %3,9, komplikasyon %14,7 oranında gözlenmiştir.…”
Section: İstatistiksel Analizunclassified
“…Another point of view was expressed by Saika et al, 16 who stated that age is not a determinant factor in the choice of the Clavien score Grade 1: any deviation of the normal postoperative course without need of pharmacological treatment or surgical, endoscopic or radiologic intervention. Treatments allowed include antiemetics, antipyretics, analgesics, diuretics, electrolytes and physiotherapy.…”
Section: Discussionmentioning
confidence: 99%